2012
DOI: 10.1158/1940-6207.capr-11-0515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cervical Human Papillomavirus (HPV) Infection in Vanuatu

Abstract: To provide information on human papillomavirus (HPV) prevalence and the distribution of individual HPV types in Pacific Islands, we conducted a population-based survey in Vanuatu, South Pacific. Nine hundred and eighty-seven women between 18 and 64 years of age were included. GP5þ -mediated PCR assay was used for HPV testing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
4
9
2
Order By: Relevance
“…Only few other studies from the region have assessed coverage of cervical cancer screening, and with the exception of Guam, these studies confirm low coverage of cervical cancer screening in the Pacific Region (Mishra et al, 2001; Balajadia et al, 2008; McAdam et al, 2010; Aruhuri et al, 2012; Hernandez et al, 2013; Law et al, 2013). A recent study from the US Affiliated Guam, American Samoa, Northern Mariana Islands, Federated States of Micronesia and Marshall Islands) examined the practices, attitudes and knowledge of health care workers on cervical cancer screening (Townsend et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Only few other studies from the region have assessed coverage of cervical cancer screening, and with the exception of Guam, these studies confirm low coverage of cervical cancer screening in the Pacific Region (Mishra et al, 2001; Balajadia et al, 2008; McAdam et al, 2010; Aruhuri et al, 2012; Hernandez et al, 2013; Law et al, 2013). A recent study from the US Affiliated Guam, American Samoa, Northern Mariana Islands, Federated States of Micronesia and Marshall Islands) examined the practices, attitudes and knowledge of health care workers on cervical cancer screening (Townsend et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…Only two studies from the Pacific Region have reported genotype prevalence in healthy women. Both studies were carried out among women in Vanuatu and may in the future serve as baseline for measuring vaccine effectiveness when the plans for HPV vaccine introduction in Vanuatu are implemented Jurisdictions (Palau, (McAdam et al, 2010; Aruhuri et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Findings can be confidently compared with other IARC HPV surveys that were conducted according to a similar sampling and HPV testing protocol. In this respect, the age-standardised HR HPV prevalence in Bhutan (18%) ranks below that of Guinea (31%) [12] and Mongolia (25%) [13], but is similar to the prevalence detected in Nigeria (18%) [14] and Vanuatu (19%) [15]. It is more elevated than that found in many other areas at high-risk for cervical cancer in Asia, including that in neighbouring countries of India (12%) [16], China (12-13%) [17-19] and Nepal (6%) [20].…”
Section: Discussionmentioning
confidence: 85%
“…The IARC has coordinated cervical cancer case series, cervical cancer case-control studies, and population-based HPV prevalence surveys in a large number of countries around the world (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); also as-yet-unpublished studies from Fiji and Bhutan). The collection of samples has spanned a period of over 20 years from 1989 until 2012 and predates the introduction of HPV vaccines.…”
Section: Methodsmentioning
confidence: 99%